Reducing medication errors in the neonatal intensive care unit - Simpson, J (2004)
Background: Medication errors are common in the neonatal intensive care unit (NICU). Various strategies to reduce errors have been described in adult and paediatric patients but there are few published data on their effect in the NICU. Aim: To describe the medication errors occurring within an NICU, and assess the impact of a combined risk management/clinical pharmacist led education programme on these errors. Methods: Medication errors were identified prospectively over one year by critical incident reporting. Four months into the study, a pharmacist led education programme was instituted. This involved a daily, cot side, pharmacist led review of medication orders. Each new member of pharmacy, nursing, or medical staff was also required to successfully complete a series of dose calculations. In addition, a risk management approach was used to make several changes in practice during the study period. Results: A total of 105 errors were identified, four serious, 45 potentially serious, and 56 minor. The four serious errors included two tenfold dose miscalculations. Most (71%) of the errors were due to poor prescribing. After the introduction of our interventions, monthly medication errors fell from a mean (SD) of 24.1 (1.7) per 1000 neonatal activity days to 5.1 (3.6) per 1000 days (p < 0.001) in the following three months. The subsequent change over of junior medical staff was associated with a significant increase in medication errors to 12.2 (3.6) per 1000 neonatal activity days (p  =  0.037). However, the number remained significantly less than before our interventions (p < 0.001). Three serious errors occurred in the first four months compared with one in the second eight month period, the latter corresponding to the six monthly change over of junior medical staff. Conclusions: Medication errors are common in NICUs. Fortunately, actual harm to an infant is rare. Interventions to reduce errors, particularly within the context of a risk management programme, are effective.